(untitled) (Research, Society and Development, 2021)
It is noteworthy that autism is a behavioral syndrome that affects neurodevelopment characterized by atypical development that can only be diagnosed by observation of a specialist responsible for detecting the autistic spectrum in children, which are characterized by three symptoms: difficulty in social interaction, quantitative deficit and qualitative communication, alteration of inappropriate behavior patterns, such as activities of restricted and stereotyped interests, which are movements of doing things repetitively and without social purpose. In its latest update—DSM-5—autism is described as a developmental disorder that leads to severe social communication impairments and restrictive, repetitive behaviors that typically begin early in life. This article brings the discussion for an effective inclusion of people with autistic spectrums that can be inserted into the educational environment in the regular education classroom and the specialized educational service by qualified professionals in order to meet the demands of inclusive education, constituting in a space of learning and development of social competence. Family members point out several weaknesses in educational inclusion that reinforce the need for the dialogue of various public policies to offer an inclusive school that promotes development and learning, given that they have an expectation of healing when the student enters the courtyards of institutions educational.